Greener Boards: Research on gender diversity and corporate environmental violations - Aulia, Zahrani; Qurrota A'yun, Annisa (Advances in Environmental Innovation, 2024)
Purpose – This study aims to examine the effect of gender diversity on boards and gender of CEOs on environmental violationsDesign/methodology/approach – The research employs a quantitative approach using regression analysis of data from 140 companies in Indonesia. Such as women on the board, female or male CEO, having environmental lawsuits, and different control variables such as size, leverage, and profitability.Findings – We find that companies with larger fractions of female directors on their corporate boards and female CEOs are sued for fewer environmental harm cases. Moreover, firms with higher rates of women in leadership are also more likely to exhibit superior environmental disclosure and more proactive sustainability measures. In particular, female chief executive officers (CEOs) spend significantly more on environmental compliance, which then reduces the likelihood of environmental violations.Originality/value – This paper adds to an increasing number of studies on gender diversity and corporate environmental sustainability, with a focus on an emerging market such as Indonesia. This allows it to find evidence for the positive impact of gender diversity in managing within business environments that are less risky to the ecology.Research Implications –  These findings have significant implications for both corporate governance and overall public policy: a move towards increased gender diversity among other senior-ranking leadership roles may indirectly promote environmentally conscious behaviour among Indonesian companies.